2014
DOI: 10.1038/onc.2014.178
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin-regulated ALDH1A1 is a target in ovarian cancer spheroids

Abstract: Cancer cells form three dimensional (3D) multicellular aggregates (or spheroids) under non-adherent culture conditions. In ovarian cancer (OC), spheroids serve as a vehicle for cancer cell dissemination in the peritoneal cavity, protecting cells from environmental stress-induced anoikis. To identify new targetable molecules in OC spheroids, we investigated gene expression profiles and networks upregulated in three dimensional (3D) versus traditional monolayer culture conditions. We identified ALDH1A1, a cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
192
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(207 citation statements)
references
References 53 publications
(57 reference statements)
10
192
0
1
Order By: Relevance
“…These subpopulations of cancer cells are believed to have CSC characteristics such as self-renewal ability and unlimited differentiation. Our group and other investigators have demonstrated that the spheroids of established ovarian cancer cell lines and transplanted human ovarian cancer possess the characteristics of OVCSLCs (3,4,(11)(12)(13)(14). In the present study, we also identified the characteristics of OVCSLCs in spheroids obtained from SKOV3 cells.…”
Section: Resultssupporting
confidence: 56%
“…These subpopulations of cancer cells are believed to have CSC characteristics such as self-renewal ability and unlimited differentiation. Our group and other investigators have demonstrated that the spheroids of established ovarian cancer cell lines and transplanted human ovarian cancer possess the characteristics of OVCSLCs (3,4,(11)(12)(13)(14). In the present study, we also identified the characteristics of OVCSLCs in spheroids obtained from SKOV3 cells.…”
Section: Resultssupporting
confidence: 56%
“…Recent studies have highlighted that cell behavior and gene expression profiles vary between cells grown in monolayers versus those that are grown as MCAs (11,23). Given that these differences result in an increased invasiveness and chemoresistance, a better understanding of how these spheroids form could lead to more effective approaches to treat the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, it is believed that interactions between various cell adhesion molecules and extracellular matrix components contribute to the formation of MCAs, including integrins, fibronectin, and cadherins (5,7,8,12). Interestingly, studies have also shown that gene and protein expression can differ between cancer cells grown in monolayers versus those within multicellular aggregates (11,13). Thus, a global comprehensive proteomics analysis that compares the proteome of the two cell populations may add to our current understanding about OvCa progression, as well as aid in the identification of novel therapeutic targets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, β-catenin-regulated ALDH1A1, a known cancer stem cell marker, has also been implicated in the formation of multicellular spheroids [48]. Recent studies suggest that tumor cells possess varying capacity for spheroid formation [45, 47,49].…”
Section: Cellular Contents: Contribution To Eoc Metastasismentioning
confidence: 99%